Dynamic responses of a flexible floating modular system subjected to ship impact. (15th November 2022) - Sun, Zhenxiang; Song, Yue; Guan, Lingyu; Huang, Guoxing; Zhang, Ningchuan
Abstract: An innovative flexible floating anti-collision system (FFAS) has been proposed and developed as restraining structure against ship direct collisions. Consisting of multiple horizontal buoy modules, the collision behaviors of the FFAS were greatly influenced by the intricate interaction between striking ship and the modular system, as well as the complicated coupling of fluid and structure. Hence, the colliding process was always oversimplified by restricting the degree of freedom and dereferencing constant added mass in the past research. To address this problem, experimental tests are conducted in a 3D water basin to build a more realistic simulation of the collision process between the FFAS and head-on navigating ship. The six-DOF motion of the stuck buoy and the tension of the block and mooring lines are synchronously monitored for hundreds of impact cases. The results indicate that the impulse load and ship sliding will occur and the impact duration and the peak tension of the lines are affected significantly. Considering various impact positions, the worst-case scenarios for the block and mooring lines are determined and the safe distance for the FFAS setup is suggested for practical design. Highlights: The impact behaviors of a flexible buoy-modular system is studied experimentally. The effect of the impact location on its anti-collision performance is highlighted. The effect of the impulse load and ship slippery on the system dynamics are examined.